Simultaneous Adalimumab and Antitubercular Treatment for Latent Tubercular Infection: An Experience from Nepal - Vaidya, Binit (Int J Rheumatol, 2019)
INTRODUCTION: In Nepal, adalimumab is the most common agent being used, but in a disease activity-based dose tapering to address the economic constraints. Another constraint is the high risk of reactivation of tuberculosis in countries with high burden, especially with the use of tumor necrosis factor blocking agents. Though there are recommendations for screening and treatment of latent tuberculosis infection (LTBI) before using adalimumab, data is not clear regarding the appropriate screening schedule and the timing of initiation of biologic therapy. METHODOLOGY: This retrospective review of prospectively followed cohort of spondyloarthropathy patients aimed to evaluate the efficacy of simultaneous initiation of adalimumab with LTBI treatment. Patients fulfilling either the modified New York criteria for ankylosing spondylitis or Assessment in SpondyloArthritis international Society criteria and who were refractory to oral treatment were screened with Mantoux (≥10mm) and interferon gamma release assay (QuantiFERON) to detected LTBI. Those who tested positive were started on rifampicin/isoniazid combination for 3 months and adalimumab treatment on the same day. The patients were followed up at 2 weeks, 4 weeks, 12 weeks, and then every 3 months for 2 years. RESULTS: Out of 784 patients diagnosed, 92 were receiving adalimumab. LTBI was detected by positivity of either Mantoux or QuantiFERON in 29.3% patients. None of the patients with LTBI who were started on the 2 drug regime simultaneous with adalimumab developed activation of tuberculosis. However, two patients testing negative for both the tests developed tubercular pleural effusion during treatment. CONCLUSIONS: Our findings indicate that screening for LTBI should be more frequent in patients from high tuberculosis burden countries; treatment of LTBI with rifampicin/isoniazid combination for 3 months is effective in preventing reactivation even when adalimumab is started simultaneously.